The moderating role of ICT on the relationship between foreign direct investment and the quality of environment in selected African countries - Aminu Hassan Jakada; Suraya Mahmood; Umar Ahmad Ali; Danmaraya Ismail Aliyu (Cogent Economics & Finance, 2023)
This empirical study examines the role of information and communication technology (ICT) in the relationship between FDI and environmental quality for six leading African economies from 1970 to 2020. The second-generation tests are used to determine the stationarity level of the variables. Furthermore, the Westerlund panel cointegration test confirms cointegration among the variables. For long-run association, CS-ARDL, which resolved the consequences of heterogeneity and cross-sectional dependency is used. The results of the study reveal that ICT, FDI, economic growth, and financial development degrade environmental quality. The interacting effect of ICT and FDI (ICT*FDI) leads to escalation of CO2 emissions thereby deteriorating the quality of the environment. The study recommends that African countries should promote FDI to support the inflow of green technologies to enhance environmental quality. The implementation of environmentally sustainable technology would help improve the quality of the environment, increase sustainability in the long term and conserve resources for future generation.
Keywords: 330; economic growth; environmental quality; FDI; ICT